Effectiveness of art therapy in improving self-esteem and alleviating anxiety among children with cancer - Paguio, Dominic Torralba (2005)
The use of art therapy in handling the psychosocial concerns of children with cancer has been done for quite some time. This study explored the effectiveness of art therapy in helping pediatric cancer patients cope with their condition. The sample consists of twenty children aged 6 to 12 and had different types of cancer. Instruments were adapted and translated versions of Gillis' Anxiety Scale and Rosenberg's Self Esteem Scale. Based on the results, art therapy is effective in alleviating anxiety and improving self esteem of girls with cancer, but not with the boys. Further studies can be done on art therapy and the detrimental psychosocial effects of cancer and other chronic illnesses on children.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Art therapy for children -- Philippines; Self-esteem in children -- Philippines; Tumors in children -- Philippines